2004
DOI: 10.1002/ffj.1300
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oils of wild and cultivated Satureja khuzistanica Jamzad from Iran

Abstract: The aerial parts were air-dried at ambient temperature in the shade and hydrodistilled using a Clevenger-type apparatus for 5 h, giving yellow oil in 0.6% yield for the wild plant and 1.2% for the cultivated plant. The oils were dried over anhydrous sodium sulphate and stored at 4-6°C. Identification of the Oil ComponentAnalytical gas chromatography (GLC) was carried out using a Hewlett-Packard HP 6890 chromatograph with a DB5 column (methyl phenyl siloxane 30 m × 0.25 mm i.d.); with a flame ionization detecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 6 publications
(5 reference statements)
1
50
0
Order By: Relevance
“…Essential oils are originating in aromatic plants and have volatile fractions that are responsible for biological activity, smell, and taste (12). Reviews have reported that the main constituents of S. khuzestanica essential oil (SKEO) in the majority species are phenols, carvacrol, thymol, p-cymene, b-caryophyllene, linalool, monoterpenes, sesquiterpenes, alcohols and phenolic acids (7,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils are originating in aromatic plants and have volatile fractions that are responsible for biological activity, smell, and taste (12). Reviews have reported that the main constituents of S. khuzestanica essential oil (SKEO) in the majority species are phenols, carvacrol, thymol, p-cymene, b-caryophyllene, linalool, monoterpenes, sesquiterpenes, alcohols and phenolic acids (7,12).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have reported that the main constituents of S. khuzestanica essential oil (SKEO) in the majority species are phenols, carvacrol, thymol, p-cymene, b-caryophyllene, linalool, monoterpenes, sesquiterpenes, alcohols and phenolic acids (7,12). On the other hand, it has been previously proven that the chemical composition of essential oils is directly depended on some factors such as the geographical source and harvesting time (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable level of essential oils, up to 4.5%, has been identified as a prominent characteristic for this plant (Hadian et al, 2011). The essential oils of Satureja khuzistanica (EOSk) were reported to be peculiarly rich in carvacrol (Farsam et al, 2004). It has been also shown that EOSk contains a spectrum of phenols, flavones, triterpenoids, steroids, and tannins (Moghaddam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Savory (Satureja khuzistanica) is an annual, herbaceous aromatic and medicinal plant belonging to the Lamiaceae family with identified essential oils named carvacrol and thymol [5] .…”
Section: öZetmentioning
confidence: 99%